1989
DOI: 10.1007/bf00249601
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity in the human lateral temporal lobe

Abstract: We have recorded neuronal responses in the lateral temporal lobe of man to overt speech during open brain surgery for epilepsy. Tests included overt naming of objects and reading words or short sentences shown on a projector screen, repetition of tape recorded words or sentences presented over a loudspeaker, and free conversation. Neuronal activity in the dominant and non-dominant temporal lobe were about equally affected by overt speech. As during listening to language (see Creutzfeldt et al. 1989), responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(116 citation statements)
references
References 10 publications
11
102
1
Order By: Relevance
“…In this study, we analyzed auditory stimuli from self-generated speech as opposed to external auditory stimulation. During self-produced speech, neural activity in human auditory cortex is reported to be suppressed (Creutzfeldt et al, 1989; Flinker et al, 2010) which has been attributed to the effect of efference copy or corollary discharge sent from the motor cortex onto sensory areas (Jeannerod, 2003). Despite this effect, we observed that high gamma activity in the superior temporal gyrus, pre- and post-central gyrus during vocalization was sufficient to reliably reconstruct continuous spectrotemporal auditory features of speech.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analyzed auditory stimuli from self-generated speech as opposed to external auditory stimulation. During self-produced speech, neural activity in human auditory cortex is reported to be suppressed (Creutzfeldt et al, 1989; Flinker et al, 2010) which has been attributed to the effect of efference copy or corollary discharge sent from the motor cortex onto sensory areas (Jeannerod, 2003). Despite this effect, we observed that high gamma activity in the superior temporal gyrus, pre- and post-central gyrus during vocalization was sufficient to reliably reconstruct continuous spectrotemporal auditory features of speech.…”
Section: Discussionmentioning
confidence: 99%
“…N1-suppression – particularly to willed vocalizations – has been interpreted as being caused by an efference copy/corollary discharge mechanism that predicts and suppresses the sensory consequences of self-generated actions. Recordings of neuronal activity in the temporal cortex during neurosurgery found that neuronal firing was suppressed during overt speech compared to passive listening (Creutzfeldt et al, 1989), and this suppression appeared to be highly localized to circumscribed areas within the auditory cortex (Chen et al, 2011; Greenlee et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Support for this mechanism comes from studies by Creutzfeldt and colleagues in which recordings were made from human patients during pre-surgical planning from the exposed surface of the right and left temporal cortices while they talked and listened to others talking; suppression of activity in auditory cortex was noted during talking compared to listening 7 . Similarly, Eliades and Wang 8, 9 recorded from primary auditory cortex single units in marmoset monkeys during vocalization, and they reported vocalization-induced suppression beginning before vocalization, with excitation of different units beginning after vocal onset 9 .…”
Section: Introductionmentioning
confidence: 99%